Pinvox Method to Enhance Self-Study in Blended Learning: Experiences at University of Bucharest - Canessa, Enrique; Logofatu, Bodgan (International Journal of Emerging Technologies in Learning (iJET), 2013)
We report results on the first large-scale trial implementation of the new Pinvox algorithm carried out at the Department of Distance Learning (DL) of the University of Bucharest to encourage hundreds of Bachelor and Master DL students to perform their self-study. Pinvox is an open source tool that helps to ensure "on-line attendanceâ? and to induce â??student’s attentionâ? through the identification of different, randomly selected, brief audio PINs embedded automatically in videos or audio files assigned to each student. We argue that checking how students watched a video lecture has many advantages in the formative assessment work.